The unique monoclonal antibodies and immunochemical assay for comprehensive determination of the cell-bound and soluble HER2 in different biological samples - Aleksandra Antos; Agnieszka Topolska-Woś; Marcin Woś; Agata Mitura; Paulina Sarzyńska; Tomasz Lipiński; Andrzej Kurylcio; Piotr Ziółkowski; Marta Świtalska; Joanna Tkaczuk-Włach; Andrzej Gamian; Wojciech P. Polkowski; et al. (Scientific Reports, 2024)
Abstract The expression of the HER2 (human epidermal growth factor receptor 2) protein in cancer cells is a well-established cancer marker used for diagnostic and therapeutic purposes in modern treatment protocols, especially in breast cancer. The gold-standard immunohistochemical diagnostic methods with the specific anti-HER2 antibodies are utilized in the clinic to measure expression level of the membrane-bound receptor. However, a soluble extracellular domain (ECD) of HER2 is released to the extracellular matrix, thus the blood assays for HER2 measurements present an attractive way for HER2 level determination. There is a need for accurate and validated assays that can be used to correlate the concentration of the circulating HER2 protein with disease clinical manifestations. Here we describe two monoclonal antibodies binding HER2 with a unique sequence of the complementarity-determining regions that recognize HER2 ECD. Development and validation of the sandwich enzyme-linked immunosorbent assay (ELISA) for quantification of the soluble HER2 in a variety of biological samples is also presented. The assay provides HER2 quantitation within a concentrations range from 1.56 to 100 ng/ml with sensitivity at the level of 0.5 ng/ml that meets the expectations for measurements of HER2 in the blood and tumor tissue samples. The method presents satisfactory intra- and inter-assay precision and accuracy for immunochemical quantification of biomarkers in biological samples. The utility of the generated monoclonal anti-HER2 antibodies has been confirmed for use in the precise measurement of HER2 (both cell-bound and soluble) in several types of biological material, including serum, solid tumor tissue, and cell culture medium. Additionally, the developed immunochemical tools have a potential for HER2 detection, not only in a wide range of sample types but also independently of the sample storage/pre-processing, allowing for comprehensive HER2 analysis in tissue (IHC), cultured cells (immunofluorescence) and blood (ELISA).